Technical Considerations in the Preliminary Design of the Pumped Storage Hydropower (PSH) - Haoyong Tian; Zaimin Ren; Chenchen Yao; Chao Wang; Meirong Li; Chunchen Xia (Hydrology)
The development of renewable energy is an effective avenue for achieving net zero goals. It requires many energy storage systems (ESSs) for adjusting the unstable power generated by renewable energy. To date, PSH is the most technically mature, economically reasonable, and reliable ESS. Currently, various countries have developed PSH. As of 2022, the global installed capacity of PSH has reached 175,060 MW, with an annual increase of 10,300 MW. This paper addresses several technical considerations in the preliminary design of PSH systems, drawing on extensive design experience. Key factors such as the selection of dam sites, installed capacity, and characteristic water levels are thoroughly discussed. These design choices are influenced by a range of factors, including geological and topographical conditions, hydrological parameters, environmental impacts, sedimentation, submersion areas, and resettlement issues. PSH is highly effective in meeting power demands, regulating frequency and phase, serving as an emergency power reserve, and improving the power factor of electrical networks. It enhances the quality of renewable energy sources such as wind, photovoltaic, and tidal power, which are characterized by intermittent supply. Beyond its technical advantages, PSH also contributes to local employment and tourism and supports pollutant reduction efforts. Compared to other energy storage systems, PSH has a more significant environmental impact and requires a longer construction period. Thus, exploring new forms of PSH is crucial. Innovative approaches such as utilizing constructed reservoirs, lakes, seas, and abandoned pits can reduce both investment and construction time while minimizing the environmental impact. This paper aims to provide some technical references and feasible plans to governments, owners, and engineers during the planning and preliminary design stages of a PSH project.